148k views
5 votes
Solve the system
2x+y=-3
-2y=6+4x

User Nefeli
by
5.2k points

2 Answers

1 vote

Answer:

0

Explanation:

Write out the 2 equations:

2x + y = -3

-2y = 6+4x

-You then pick a variable that you want to solve for. I chose to solve for y because it would be a bit easier.

-2y = 6 + 4x

-Divide both sides by -2 to isolate the variable

(-2y) / -2 = (6 + 4x) / -2

-it comes out to y = -3 -2x

-Now that you have the y you can plug in the value into the second equation.

2x + y = -3 ---> 2x + (-3 -2x) = -3

This can be simplified to:

2x - 3 - 2x = -3

The 2x's cancel out because there is a +2x and a -2x. You are left with a

-3 = -3. If you add 3 to both sides of the equation you end up with 0 = 0, which can be simplified to just 0.

User Chakreshwar Sharma
by
4.6k points
0 votes

Answer:

Write each equation in slope-intercept form.

-2x + -3

-2x + -3

What do the equations have in common?

- The slopes are the same.

- The y-intercepts are the same

- The lines are the same.

The system represents lines that

✔ coincide therefore the system has

✔ infinitely many solutions.

User Daniel Widdis
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.